Solvability of Some Perturbed Generalized Variational Inequalities in Reflexive Banach Spaces - Xue-ping Luo (Journal of Function Spaces)
This paper aims to discuss the solvability of some perturbed generalized variational inequalities with both the mapping and the constraint set perturbed simultaneously in reflexive Banach spaces, under some coercivity conditions. In particular, a new result that the set is directional perturbed is presented. The main results generalize and extend some known results in this area.